(untitled) (Archive of Conferences, 2021)
This article focuses on the interrelationships of components such as mastery, fragmentation, repetition and consolidation for modern lessons, acquisition of new learning material and control of previously learned in relation to its practical application. answers to questions such as what is modern education, the difference between traditional education and modern education. Students’ independent work is organized not only in the stages of repetition and consolidation, but also in the process of learning new material, thereby establishing a strong link between teaching and learning, the team work of the class and the individual work of the student enhancements and opportunities are highlighted.